The Travelling Metaphor in Contemporary Terminology - Butiurca Doina (Acta Universitatis Sapientiae: Philologica, 2015)
External motivation, the classification and characteristics of this type of motivation - attributed to an impressive number of specialized terms in contemporary scientific languages - is the topic we propose to approach in our study. The motivated relationship between the signified object and the term and the metasemic motivation (in the case of change of meaning) are two of our general research directions. The definition of the metasemically motivated “travelling” metaphor in terminology, the cultural sources of this type of metaphor, the patterns of interdisciplinarity it creates in the corpus of terms and/or specialized discourse, and the multi- and plurilingual dimension represent the specific objectives of our research (applicative and theoretical). The descriptive-linguistic method, the contrastive method are the methods applied in the study to show the extent to which the condition of precision of the specialized meaning is met in the different languages. The results of this research reveal that external motivation, the metaphor, represents one of the creative forces of present terminology.